2021
DOI: 10.1111/apha.13637
|View full text |Cite
|
Sign up to set email alerts
|

Renal handling of nitrate in women and men with elevated blood pressure

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…Compared with HV, acute intake of nitrate was associated with significantly higher maximal plasma concentrations for nitrate and nitrite in HD patients as well as higher AUCs of these anions. Circulating nitrate (and nitrite) is mainly eliminated via the kidneys [41,42]. Therefore, the increased plasma concentrations of these two anions observed in our HD patients is most likely due to their full loss of residual renal function.…”
Section: Discussionmentioning
confidence: 82%
“…Compared with HV, acute intake of nitrate was associated with significantly higher maximal plasma concentrations for nitrate and nitrite in HD patients as well as higher AUCs of these anions. Circulating nitrate (and nitrite) is mainly eliminated via the kidneys [41,42]. Therefore, the increased plasma concentrations of these two anions observed in our HD patients is most likely due to their full loss of residual renal function.…”
Section: Discussionmentioning
confidence: 82%
“…Co-administration of L-NAME and L-Arg showed no inflammatory effects, which may be due to the inhibitory effect of L-NAME on NO production from L-Arg so it can be concluded that L-NAME and similar compounds can be used to reduce NO-induced tissue damage. This feature has been used in various studies to reduce the pathological complications of NO [9].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that there is evidence for a substantial nitrate sparing capacity of the kidneys, which is higher in women compared to men. 1 The study did not give any explanation about the underlying mechanisms which need to be resolved in future work.…”
mentioning
confidence: 87%
“…Nitric oxide (NO) is still regarded to be an important signaling molecule in blood pressure regulation and many aspects of its regulation are still unknown. The inorganic anions nitrate and nitrite are oxidation products of NO that have often been used as an index of NO generation 1 . The aim of a study by Sundqvist et al, was to explore potential sex differences in renal nitrate handling during low and high dietary nitrate intake.…”
mentioning
confidence: 99%
See 1 more Smart Citation